2016
DOI: 10.5414/cn108795
|View full text |Cite
|
Sign up to set email alerts
|

Care and outcomes of end-stage kidney disease patients in times of armed conflict: recommendations for action

Abstract: ESKD patients, especially dialysis patients, comprise a severely vulnerable population during conflicts. Their care can be disrupted and altered leading to a substantial increase in their mortality rate. Efforts to improve their care during conflicts are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Regional and international renal professionals and organizations should play a major role in optimizing the provision of care, education, advocacy, and research. 4 Examples of such efforts include finding ways to get cheaper supplies, especially for peritoneal dialysis; lobbying governments and international organizations to provide protection for this vulnerable population; conducting research on cheaper alternatives, such as lower dialysis dose and low hemoglobin goals; and advocating palliative care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional and international renal professionals and organizations should play a major role in optimizing the provision of care, education, advocacy, and research. 4 Examples of such efforts include finding ways to get cheaper supplies, especially for peritoneal dialysis; lobbying governments and international organizations to provide protection for this vulnerable population; conducting research on cheaper alternatives, such as lower dialysis dose and low hemoglobin goals; and advocating palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…3 Studies from the Syrian War and other wars showed a major negative impact on the populations with ESRD of the war-torn countries including excess death, loss of facilities, and diminution of the workforce. 4 , 5 As a result, many patients with ESRD seek refuge in other countries. The size and gravity of the problem of patients who need dialysis becoming refugees were recently highlighted in a survey of providers in Europe and the Middle East done by the Renal Disaster Relief Task Force of the International Society of Nephrology and European Renal Association/European Dialysis and Transplant Association.…”
mentioning
confidence: 99%
“…Literature on best practices for continuing medical care during war is scarce [ 6 ], especially for non-communicable diseases [ 5 ]. War conflicts in Iraqi–Kuwait, Bosnia and Herzegovina, Syria, and Yemen were characterized by damaged general infrastructure, disorganization, chaos, lack of electricity, fuel and clean water, and shortages of supplies, medications, diagnostic tools and medical personnel [ 6 , 7 ]. Blockades of humanitarian aid and attacks on healthcare facilities and medical personnel were also used as a military strategy [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the influx of Syrian refugees has already overstretched the capacity of the highly privatized health-care system in Lebanon. 5 , 6 Disruption of dialysis sessions might lead to a substantial increase in deaths; 7 however, current interventions, including our programme, are not able to cover all the needs for the management of chronic renal failure among the refugees in Lebanon. A recent survey on the medical and psychosocial challenges of 57 Syrian refugees who required dialysis in Jordan, showed that 14 patients (25% of those surveyed) had at least one period of dialysis interruption of a week or more, with financial reasons being the most common cause.…”
mentioning
confidence: 99%